Incidence and Risk Factors for Prolonged Opioid Use after Arthroscopic Meniscal Surgery: An Analysis of 107, 717 Cases. Issue 7 (31st July 2020) - Baron, Jacqueline; Shamrock, Alan; Gulbrandsen, Trevor; Wolf, Brian; Duchman, Kyle; Westermann, Robert; Khazi, Zain
Objectives: The current opioid epidemic in the United States is a significant cause of increasing morbidity and mortality. The purpose of this study was to determine rate of opioid use before and after arthroscopic meniscal surgery, and assess patient factors associated with prolonged opioid use following primary arthroscopic meniscal surgery. Methods: Patients undergoing primary arthroscopic meniscal surgery procedures from 2007-2016 were retrospectively accessed from the Humana Inc. administrative claims database. Patients were categorized as patients who filled opioid prescriptions within 3 months (OU), within 1 month (A-OU), between 1 to 3 months (C-OU), and never filled opioid prescriptions (N-OU) before surgery. Rates of opioid use were evaluated preoperatively and longitudinally tracked for OU and N-OU cohorts. Prolonged opioid use was defined as continued opioid prescription filling at ≥3 months after surgery. Multiple logistic regression analysis was used to control for various patient characteristics and identify factors associated with opioid use at 12 months after surgery, with significance defined as P<0.05 Results: There were 107, 717 patients (54% female) that underwent arthroscopic meniscal surgery during the study period, of which 46.1% (n=49, 630) were N-OU. One year after surgery, opioid fill rate was significantly higher in the OU group compared to the N-OU group with a relative risk of 6.98 (21.1% vs 3.02%; 95% CI: 6.61-7.36; p<0.0001). Multiple logistic regression model identified C-OU (OR:10.23, 95% CI: 9.74-10.76, p<0.0001) as the strongest predictor of opioid use at 12 months postoperatively. Furthermore, patients with acute preoperative opioid use (p<0.0001), preoperative diagnosis of diabetes mellitus (p<0.0001), hypertension (p<0.0001), chronic obstructive pulmonary disease (p<0.0001), anxiety or depression (p<0.0001), alcohol abuse (p= 0.0019), and tobacco use (p=0.0345) had a significantly increased odds of opioid use at 12 months postoperatively. However, males (p<0.0001) and patients <40 years (p<0.0001) had a significantly decreased odds of opioid use 12 months postoperatively. Conclusion: Preoperative opioid use is a significant risk factor for opioid use at 12 months following surgery. Diabetes mellitus, hypertension, chronic obstructive pulmonary disease, smoking status, and psychiatric diagnosis were independent risk factors for opioid use 1-year following surgery.